The relationship of lactic acid to long-distance swimming and the 2 x 400-m-"2-speed test" and the implications for adjusting training intensities - Olbrecht, J.; Mader, A.; Madsen, Oe.; Liesen, H.; Hollmann, W. (Swimming Science V, 1988)
The concentration of lactic acid has been used not only to control the sport-specific performance capacity of athletes (Keul, Kindermann, & Simon, 1978; Madsen, 1982; Margaria, 1976; Saltin, 1973; Stegmann & Kindermann, 1982) but also to determine the optimal training intensity (Fohrenbach, Mader, & Hollmann, 1981; Keul et al., 1979; Uesen, Mader, Heck, & Hollmann, 1977; Mader, Madsen, & Hollmann, 1980; Madsen & Olbrecht, 1983). Not everyone, however, can make use of this method. Therefore, an attempt was made to find an alternative method-a type of test, without any lactate measurements, that could be used to adapt individual training intensities to the endurance capacity of each athlete. The present study compared the relationship between swimming speed and lactic acid accumulation during the 2 x 400-m "2-speed test" (Mader et al., 1980) and during 30 and 60 min of continuous swimming. In accordance with the changes in the relationship between lactate and speed in prolonged and interval-type exercises (Olbrecht, Madsen, Mader, Uesen, & Hollmann, 1985), a range of intensities was established for different types of endurance training for the tested athletes.